Polyvinylpyrrolidone-assisted synthesis of highly water-stable cadmium-based metal–organic framework nanosheets for the detection of metronidazole. Issue 55 (27th October 2021) - Qin, Guoxu; Cao, Duojun; Wan, Xinjun; Wang, Xinyun; Kong, Yaqiong
Abstract : Except PVP was added for Cd-MOF nanosheets, the preparation process of bulk and Cd-MOF nanosheets was similar. Abstract : Recently, much effort has been dedicated to ultra-thin two-dimensional metal–organic framework (2D MOF) nanosheets due to their outstanding properties, such as ultra-thin morphology, large specific surface area, abundant modifiable active sites, etc. However, the preparation of high-quality 2D MOF nanosheets in good yields still remains a huge challenge. Herein, we report 2D cadmium-based metal–organic framework (Cd-MOF) nanosheets prepared in a one-pot polyvinylpyrrolidone (PVP)-assisted synthesis method with high yield. The Cd-MOF nanosheets were characterized with good stability and dispersion in aqueous systems, and were highly selective and sensitive to the antibiotic metronidazole (MNZ) with low limit of detection (LOD: 0.10 μM), thus providing a new and promising fluorescent sensor for rapid detection of MNZ in aqueous solution.